The Family behind the Family Firm: Evidence from CEO Transitions - Morten Bennedsen; Kasper Nielsen (Copenhagen Business School (CBS), Department of Economics, 2004)
Economists have long acknowledged that the structure of the family (number of offspring, marital status, etc.) plays a crucial role in important economic decisions (e.g., labor supply, demand patterns, portfolio choice, educational attainment). In this paper we investigate the link between family structure and corporate decisions of family firms. Even though there is considerable anecdotal evidence on this link, there is no systematic study. This paper fills this gap. To this end, we assembled a unique dataset with accounting information from 1995 to 2002 of the universe of privately held firms in Denmark. Our dataset includes the family trees of the owners as well as personal information about all family members. This information allows us to identify family firms among privately held firms. We find that, using a 50% definition of control, 89% of privately held firms are family firms. We focus on the decision whether to choose a family member or an outsider as the next CEO. We show that the larger the pool of potential heirs, the higher the probability of family transition. Also we document that this probability is significantly lower when all offspring are female. Finally, family conflicts (proxied by divorce or multiple marriages) reduce the probability of family transition. In a robustness check we show that there is a causal effect from family structure to corporate decisions. We do this by instrumentimg the number of children with sibling sex composition and by restricting the sample to one in which founders had their last child years before founding the firm.
hdl:10398/7631
Keywords: G10; 330